Earlier‐ born secondary hair follicles exhibit phenotypic plasticity. Issue 4 (12th January 2015) - Chi, Woo; Wu, Eleanor; Morgan, Bruce A.
Abstract: The mouse pelage is composed of four distinct hair types. The fact that the follicles that generate these hair types form in successive waves during late embryonic development suggested the model that distinct epigenetic states of the inductive mesenchyme fixed when the follicles are formed specify the distinctive hair morphologies. This model is inconsistent with the observation that many follicles produce different hair types in successive hair cycles. In this study, the characteristics of the hair follicles that switch between the production of different hair types were examined. These follicles were born earlier than those that do not switch between hair types and made longer hairs. They also expressed a higher level of Sox2 in the dermal papilla and had more DP cells per follicle. These observations are consistent with the hypothesis that different birthdates specify the potential of different follicles. However, rather than directly specifying hair type, birthdate correlates with three types: guard hairs, a plastic population that can make awl, auchene or zigzag hairs, and a population that normally makes only zigzag hairs. Although Sox2 expression levels in the DP identify this subset during the morphogenetic cycle, Sox2 expression is not a fixed epigenetic state specified when the follicle is first formed.